PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI WIRAUSAHA TERHADAP DAYA SAING - Dwi Novitasari; Lukia Zuraida (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2015)
Small and Medium Enterprises (SMEs) cannot be separated from entrepreneur and entrepreneurial terms. Many factors influence of SMEs development, both internally and externally. This study tends to observe from internal side, where a factor of entrepreneurship orientation and entrepreneurial competence has had an important role. Dimensions of entrepreneurship orientation are: need for achievement, internal locus of control, self reliance and extroversion. Entrepreneurship orientation is basis that should be owned by every entrepreneur to run their business and the other hand created the competitiveness of SMEs. The need for adequate competence in running a business is considered an urgent thing started, because by having sufficient competence expected of entrepreneurs able to compete both locally and globally. Dimensions competencies are: task/skill, task management skills, contingency management skills, job role environment skills, and transfer skills. By growing and advancement of the business activities of SMEs is an interesting topic to be researched, each of effort is required to have a distinctive competitiveness and unique. To determine competitiveness dimensions includes: valuable resource, rare, difficult to imitate and non-substitutable. The results showed that the entrepreneurship orientation (with a significance value of 0.005) and entrepreneurial competencies (with a significance value of 0.000) have an influence on competitiveness. By knowing the extent of the influence of entrepreneurial orientation and entrepreneurial competence on the competitiveness of SMEs in DIY, it is expected to help the government, private sector and academicians in facilitating and supporting the development of SMEs in DIY.